Studying the effect of institutional pressures on the intentions to continue green information technology usage - Abdul Aladheem Driafish Jabbar Alziady; Sabah H. Enayah (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
The last decade witnessed the emergence of green information technology(GIT) which includes organizational initiatives to reduce the negative impact of information technology (IT) on the environment. GIT has gained considerable interest among researchers because of a huge negative impact on the environment and an extensive use of information technology. A research instrument has been developed to link three components: coercive pressure, normative influence, and mimicry and stdy their effect on GIT adopt and continuance intentions. The model is validated using data collected from a field survey of 99 managers of small enterprises (SEs) in Thi-Qar province. The analysis that normative pressures are the most influential in the adoption of green IT. The coercive pressures have the most significant effect on the continuance usage of GIT practices. The current study would contribute to illustrate knowledge in the field of IT, regarding the decision maker's intention for the adoption and continue using GIT through the development of a theoretical framework that identified the key factors of GIT adoption and intention continuance.
Keywords: 650; Green information technology; Institutional pressures